Pemahaman Karakteristik Hujan Sebagai Dasar Pemilihan Model Hidrologi (Studi Kasus di Das Bengawan Solo Hulu) - M Pramono Hadi (Forum Geografi, 2006)
The research was conducted at the Upper Bengawan Solo Catchment, which was categorized as critical catchment. The problems of flood and drought became the main issue, and need to be handled sooner, therefore it need hydrological modelling to coupe the problems. As we know that the role of rainfall as an input to the model is very significant parameter in generating output (discharge), then the objective of this research is to know the rainfall characteristics. The rainfall distribution in the research area can be known by doing the spatial analysis, especially using Kriging method. It does the rainfall mapping for a certain duration to describe the spatial rainfall distribution. It uses the rainfall data from 20 rainfall stations with 5 minutes interval recording. It does the inter-stations correlation analysis on the amount of rainfall and the distance of inter-stations. The significant level used in this study is 5%. The result shows the tendency that the more of the station number decreased, the smaller the rainfall correlation coefficient inter-stations are. It can be meant that the numbers of the rainfall stations in catchment area have optimum number of gauge. The coverage area for each station is 13 km2 when we use 5’s minute interval data. Most of the rainfall which have intensity 30 mm/hr occur at minute 20th to 125th. As much as 17.5% of these rainfall have randomly distribution. There is a significant relationship (R2=65.2%) between daily maximum rainfall and minimum values of inter-stations correlation coefficient Base on above results it is very important to consider that in chosing the size of catchment area for hydrological modeling it should be related with its rainfall chracteristics.